AL-AMR BI AL-SYIRA’ FROM THE PERSPECTIVE OF AGENCY THEORY - Asnan Purba; Oyo Sunaryo Mukhlas; Burnahnuddin (International Journal of Multidisciplinary Reseach, 2026)
This study examines the practice of al-amr bi al-syirāʾ (murābaḥah to purchase orderer), particularly murābaḥah bil wakālah, through the lens of Agency Theory and Islamic legal frameworks. The rapid expansion of Islamic banking in Indonesia has led to the dominant use of murābaḥah financing, often combined with wakālah to enhance operational efficiency. However, this hybrid structure raises concerns regarding agency problems, information asymmetry, and substantive Sharīʿah compliance. Using a qualitative approach, this research integrates literature review and content analysis of primary regulatory sources, including the Compilation of Sharia Economic Law (KHES), DSN-MUI fatwas, and AAOIFI Shariʿah and accounting standards, supported by relevant academic literature. The findings reveal two contrasting regulatory approaches. The KHES and DSN-MUI frameworks emphasize flexibility and maṣlaḥah by allowing legal ownership (qabḍ ḥukmī) and delegated purchasing, which reduces transaction costs but increases agency risks such as moral hazard. In contrast, AAOIFI adopts a conservative stance that requires substantive ownership (qabḍ ḥaqīqī) and full risk assumption by Islamic financial institutions, thereby minimizing agency problems at the expense of higher operational costs. This study contributes to the literature by highlighting the trade-off between efficiency and agency cost in murābaḥah practices and underscores the need for harmonization between local and international standards to ensure both Sharīʿah compliance and effective risk governance in Islamic financing.